Flavonoids and Polyphenolic Compounds as Potential Talented Agents for the Treatment of Alzheimer’s Disease and their Antioxidant Activities - Akter, Rokeya; Chowdhury, Md. A. R.; Rahman, Md. H. (Current Pharmaceutical Design, 2021)
Aging is a normal human cycle and the most important risk factor for neurodegenerative diseases. Alternations in cells due to aging contribute to loss of the nutrient-sensing, cell function, increased oxidative stress, loss of the homeostasis cell, genomic instability, the build-up of malfunctioning proteins, weakened cellular defenses, and a telomere split. Disturbance of these essential cellular processes in neuronal cells can lead to life threats including Alzheimer's disease (AD), Huntington's disease (HD), Lewy's disease, etc. The most common cause of death in the elderly population is AD. Specific therapeutic molecules were created to alleviate AD’s social, economic, and health burden. In clinical practice, almost every chemical compound was found to relieve symptoms only in palliative treatment. The reason behind these perfect medicines is that the current medicines are not effective in targeting the cause of this disease. In this paper, we explored the potential role of flavonoid and polyphenolic compounds, which could be the most effective preventative anti-Alzheimer 's strategy.
Keywords: amyloid-β